Strengthening the Rule of Law and Preventing Violations in the Sphere of Administrative and other Public Legal Relations is the Most Important Task of Administrative Legal Proceedings - O. S. Rogacheva (Courier of Kutafin Moscow State Law University (MSAL)), 2026)
The topic of strengthening the rule of law and preventing violations in the field of administrative and other public legal relations in administrative proceedings occupies a key place in modern science of administrative and administrative procedural law. With the adoption of the Code of Administrative Procedure of the Russian Federation, the analyzed task as an element of the procedural form of administrative proceedings acquires strategic importance both for protecting the rights, freedoms and legitimate interests of citizens, the rights and legitimate interests of organizations, and for ensuring the rule of law in the field of activities of public administration bodies. Considering disputes between citizens and the state, the court not only protects the person, but also educates the oﬃcial, forming the standards of his lawful behavior. The verdict on challenging the actions of the authorities is addressed not only to the parties to managerial legal relations, but also to an indefinite number of oﬃcials of public administration bodies, for whom it acquires orienting significance in order to carry out proper public administration. A key but not conceptually elaborated function of administrative justice is the prevention of torts in public administration. We are talking about a preventive effect on the system of public administration, including organizations vested with authority. In the context of expanding administrative discretion and complicating the public functions of the state, the formation of anti-crisis public administration, the preventive potential of administrative proceedings is of particular importance.